Ambient groundwater flow diminishes nitrate processing in the hyporheic zone of streams. Issue 5 (15th May 2017) - Azizian, Morvarid; Boano, Fulvio; Cook, Perran L. M.; Detwiler, Russell L.; Rippy, Megan A.; Grant, Stanley B.
Abstract: Modeling and experimental studies demonstrate that ambient groundwater reduces hyporheic exchange, but the implications of this observation for stream N‐cycling is not yet clear. Here we utilize a simple process‐based model (the Pumping and Streamline Segregation or PASS model) to evaluate N‐cycling over two scales of hyporheic exchange (fluvial ripples and riffle‐pool sequences), ten ambient groundwater and stream flow scenarios (five gaining and losing conditions and two stream discharges), and three biogeochemical settings (identified based on a principal component analysis of previously published measurements in streams throughout the United States). Model‐data comparisons indicate that our model provides realistic estimates for direct denitrification of stream nitrate, but overpredicts nitrification and coupled nitrification‐denitrification. Riffle‐pool sequences are responsible for most of the N‐processing, despite the fact that fluvial ripples generate 3–11 times more hyporheic exchange flux. Across all scenarios, hyporheic exchange flux and the Damköhler Number emerge as primary controls on stream N‐cycling; the former regulates trafficking of nutrients and oxygen across the sediment‐water interface, while the latter quantifies the relative rates of organic carbon mineralization and advective transport in streambed sediments. Vertical groundwater flux modulates both of these master variables in ways that tend to diminish stream N‐cycling. Thus, anthropogenic perturbations of ambient groundwater flows (e.g., by urbanization, agricultural activities, groundwater mining, and/or climate change) may compromise some of the key ecosystem services provided by streams. Plain Language Summary: Humans generate vast quantities of bioavailable nitrogen for agricultural production, and much of the excess ends up in rivers and streams. As the nitrogen flows downstream, some of it is naturally removed by streambed sediments through a process known as hyporheic exchange. In this paper, we set out to answer the question: how does the movement of groundwater into (or out of) a stream affect the removal of nitrogen by hyporheic exchange? Multiscale and multi‐physics model simulations suggest that groundwater movement across the streambed can "shut down" the physical and biological processes that remove stream nitrogen. Hence, stream‐groundwater interactions may play an important role in modulating the human and environmental impacts of nitrogen pollution. Key Points: Nitrate uptake velocities are simulated using a modeling framework that accounts for hyporheic exchange and ambient groundwater flow Fluvial ripples dominate hyporheic exchange flux, but riffle‐pool sequences dominate the turnover of nitrate and ammonium in streambed sediments The Damköhler Number and hyporheic exchange flux are primary controls on N‐cycling, but both are influenced by ambient groundwater flow